The Morphology and Conductive Properties of Composite Material SiO2 – C - Myronyuk, I.F.; Mandzyuk, V.I.; Sachko, V.M.; Kyluk, Yu.O. (Physics and Chemistry of Solid State, 2015)
The article explores the structure, morphology and conductive properties of composite material SiO2 – C using XRD, SAXS, low-temperature nitrogen adsorption, and impedance spectroscopy methods. It is set that SiO2 – C composite obtained by thermolytic decomposition of D-lactose, previously chemisorbed on fumed silica nanoparticles surface, has an open porous structure, in which mesopores of 6-12 nm in size are dominate. At weight ratio SiO2/C = 5/1 nanocrystallites of carbon phase in form of lamellar sheets of 0,4 × 0,4 × 5,0 nm3 in size contact with entire silica surface that results in composite material conductivity is 49 Оhm-1·m-1.